Feasibility, Fidelity and Acceptability of a Person‐Centred Care Transition Support Intervention for Stroke Survivors: A Non‐Randomised Controlled Study - Sebastian Lindblom; Maria Flink; Lena vonKoch; Ann Charlotte Laska; Charlotte Ytterberg (Health Expectations)
ABSTRACT Background Care transitions from hospital to home are a critical period for patients and their families, especially after a stroke. The aim of this study was to assess the feasibility, fidelity and acceptability of a co‐designed care transition support for stroke survivors. Methods A non‐randomised controlled feasibility study recruiting patients who had had stroke and who were to be discharged home and referred to a neurorehabilitation team in primary healthcare was conducted. Data on the feasibility of recruitment and fidelity of the intervention were collected continuously during the study with screening lists and checklists. Data on the perceived quality of care transition were collected at 1‐week post‐discharge with the Care Transition Measure. Data on participant characteristics, disease‐related data and outcomes were collected at baseline (hospitalisation), 1 week and 3 months post‐discharge. Data on the acceptability of the intervention from the perspective of healthcare professionals were collected at 3 months using the Normalisation Measure Development Questionnaire. Results Altogether, 49 stroke survivors were included in the study: 28 in the intervention group and 21 in the control group. The recruitment and data collection of patient characteristics, disease‐related data, functioning and outcomes were feasible. The fidelity of the intervention differed in relation to the different components of the co‐designed care transition support. The intervention was acceptable from the perspective of healthcare professionals. Concerns were raised about the fidelity of the intervention. A positive direction of effects of the intervention on the perceived quality of the care transition was found. Conclusion The study design, data collection, procedures and intervention were deemed feasible and acceptable. Modifications are needed to improve intervention fidelity by supporting healthcare professionals to apply the intervention. The feasibility study showed a positive direction of effect on perceived quality with the care transition, but a large‐scale trial is needed to determine its effectiveness. Patient or Public Contribution Stroke survivors, significant others and healthcare professionals were involved in a co‐design process, including the joint development of the intervention's components, contextual factors to consider, participant needs and important outcomes to target. Trial Registration ClinicalTrials.gov ID: NCT0292587.